Gender and Ethnic Disparities of Acute Kidney Injury in COVID-19 Infected Patients: A Literature Review - He, Weihang; Liu, Xiaoqiang; Hu, Bing; Li, Dongshui; Chen, Luyao; Li, Yu; Zhu, Ke; Tu, Yechao; Xiong, Situ; Wang, Gongxian; Fu, Bin (Frontiers in Cellular and Infection Microbiology, 2022)
Coronavirus disease 2019(COVID-19) has become a public health emergency of concern worldwide. COVID-19 is a new infectious disease arising from Coronavirus 2 (SARS-CoV-2). It has a strong transmission capacity and can cause severe and even fatal respiratory diseases. It can also affect other organs such as the heart, kidneys and digestive tract. Clinical evidence indicates that kidney injury is a common complication of COVID-19, and acute kidney injury (AKI) may even occur in severely ill patients. Data from China and the United States showed that male sex, Black race, the elderly, chronic kidney disease, diabetes, hypertension, cardiovascular disease, and higher body mass index are associated with COVID-19‐induced AKI. In this review, we found gender and ethnic differences in the occurrence and development of AKI in patients with COVID-19 through literature search and analysis. By summarizing the mechanism of gender and ethnic differences in AKI among patients with COVID-19, we found that male and Black race have more progress to COVID-19-induced AKI than their counterparts.